Strategy For Development of Orchid Ornamental Plant (Case Study of UPTD BBIH, Amoito Village, Ranomeeto District, South Konawe Regency) - Sri, Sri; Rianse, Usman; Yusria, Waode (Department of Agribusiness, Halu Oleo University, 2021)
This study aims to determine the strategy for developing ornamental orchids in UPTD BBIH, Amoito Village, Ranomeeto District, South Konawe Regency. This research is a case study on ornamental orchid plants determined on purpose (purposive sampling). Data analysis used the SWOT Analysis to determine the criteria and prospect alternatives that are the most priority for ornamental orchid plants. Based on the results of the identification of internal and external factors that determine the prospects for the development of ornamental orchids at UPTD BBIH, Amoito Village, Ranomeeto District, Konawe Selatan Regency, internal factors were found, namely the absence of technical guidance for workers, lack of service facilitation between product messages, using the availability of business capital and utilizing bonus purchase of ornamental plants orchids. While external factors are the lack of labour recruitment, the existence of a marketing network, using online media as promotion, and developing product creativity through exhibitions.